How to avoid statin hepatotoxicity in patients with obesity and liver disease? Focus on the combination of ursodeoxycholic acid and atorvastatin - O. N. Korneeva; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2012)
Obese patients demonstrate the combination of dyslipidemia (DLP) and elevated transaminase levels, as a manifestation of non-alcohol fatty liver disease (NAFLD). Therefore, statins should be administered with care in this clinical group. In the real-world clinical practice, obese patients with high cardiovascular risk and concomitant NAFLD often receive low, inadequately effective doses of statins, due to the fear of their adverse effects on the hepatic function. An alternative method of DLP treatment is a combination of statins with ursodeoxycholic acid (UDCA). The need for a long-term combination treatment with statins and UDCA stresses the importance of the problem of drug interaction and the mechanisms of drug metabolism. Even high doses of atorvastatin are safe and well tolerated. The most severe adverse effects – myopathy and rhabdomyolysis – are very rare. Currently, there is no available evidence of adverse clinical effects of the combination of UDCA and atorvastatin. Presented results emphasise the need for a wider use of new therapeutic strategies in patients with DLP, obesity, and NAFLD. The combination of UDCA and statins is safe and effective. It facilitates not only the achievement of target lipid levels, but also the improvement in the hepatic function.